PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA BELANJA DAN USAHA ONLINE BAGI WKRI GEREJA GYB SURABAYA - Nugraheni, Yuli; Yuliastuti, Maria; Akhsaniyah, Akhsaniyah; Evania, Angela; Mevelyn, Alexandra; Hana, Benedicta (Universitas katolik Musi Charitas, 2022)
The emergence of the Covid-19 pandemic has forced members of the Catholic Women of the Republic of Indonesia (WKRI) Surabaya Branch of the Good Shepherd Catholic Church (GYB) to adjust to implementing new habits. However, due to limited knowledge of the ability to understand how to shop online and create interesting online media content as a means of online promotion, the WKRI Branch of the Good Shepherd Catholic Church Surabaya is very need help producing content. Departing from this need, the community service team of the Widya Mandala Catholic University Communication Studies Program provided training for the WKRI Branch of the Good Shepherd Catholic Church Surabaya. The training method provided is through mentoring the use of online shopping applications and creating interesting content, including making headlines, photos and videos as online promotional materials. With the ability to shop online, you will be able to save time, energy and costs. And the ability to make good headlines, photos and videos can be used as a means of online promotion to increase the business of WKRI members. After the training, mothers are able to use online shopping applications and create interesting promotional content on social media in the form of headlines, photos and videos. The Abdimas team suggested that research based on the results of this abdimas be carried out to examine the level of knowledge, attitudes, and preferences of WKRI members regarding the selection of information and social media choices